Cambio en la actividad física durante la vida universitaria del estudiante de medicina de la Universidad Nacional de Trujillo - Verástegui Morales, Jessica Violeta (2014)
Determine the change in physical activity during college life of medical student at the National University of Trujillo. Material and Method: An observational, descriptive, cross-sectional retrospective study was performed. The sample selection was random and draw method. Participants, in accordance with the inclusion and exclusion criteria; they respond to two questionnaires; the first of 35 open and closed questions to answer regarding the target change in physical activity during college life and in terms of interests and motives: and IPAQ short version questionnaire which will determine the type and level of physical activity in wherein each participant is located. Data were processed using SPSS V 17 package and the results presented in two-way tables according to the objectives; also bar and pie charts were used for better visualization of the results. Analysis and interpretation of data with chi-square test statistic, and significance of the 95% confidence level. Results: The change in physical activity in first, third and sixth year gives us a value of p <0.05 therefore is a significant relationship between years of study and time spent on physical activity: the level of physical activity with IPAQ questionnaire of the total sample 34.3% had low level of physical activity, 17.0% medium and 48.6% high level of physical activity; 37% of the sample were women, of whom 55.1% had low level of physical activity, 17.2% medium and 27.6% high; 63% of the sample were men, of these 18% had low level of physical activity, 18% medium and 64% high. In relevance to the practice of physical activity, soccer was the main one with 30% and then swimming with 29%. From the total sample 56% prefer physical or sporting activity instructor rather than activities not directioned, 71% in group and 56% says prefer organized competitions. About motivation, 13 students had preferences for sport like a routine and 13 students just for fun. Conclusions: The time spent on physical activity decreases significantly during the years of university study